Minimum Muscular Fitness of Secondary Level Students - Bhatt, Mahesh Datt; Datt, Tara (Tribhuvan University Journal, 2016)
This paper deals with the minimum muscular fitness of secondary level students of Birendranagar Municipality of Surkhet of Nepal. Two hundred fifty five secondary level students were tested with Kraus-Weber tests for their minimum muscular fitness. The age of the students was thirteen to eighteen years. The results revealed that 71.03 percent boys and 62.73 percent girls had minimum muscular fitness. Among the tested subjects 35.94 percent Bhraman-Chhetri, 25.86 percent Janajati and31.89 percent Dalit did not have the minimum muscular fitness. Weakness plays a significant role than the flexibility not to gain minimum muscular fitness to the subjects.